2020
DOI: 10.1161/strokeaha.120.029262
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Commensal Bacterial Signature in the Gut Is Associated With Acute and Long-Term Protection From Ischemic Stroke

Abstract: Background and Purpose— Commensal gut bacteria have a profound impact on stroke pathophysiology. Here, we investigated whether modification of the microbiota influences acute and long-term outcome in mice subjected to stroke. Methods— C57BL/6 male mice received a cocktail of antibiotics or single antibiotic. After 4 weeks, fecal bacterial density of the 16S rRNA gene was quantitated by qPCR, and phylogenetic classification was obtained by 16S rRNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 34 publications
4
71
0
Order By: Relevance
“…It has been demonstrated that adjustments in the gut microbiome influence ischemic brain injury by altering immune homeostasis (Benakis et al, 2016;Singh et al, 2016) and neuroprotective cytokine production (Benakis et al, 2016). This suggests that the gut microbiome is another potential therapeutic target for stroke (Benakis et al, 2016;Singh et al, 2016Singh et al, , 2018Winek et al, 2016;Benakis et al, 2020). Studies of gut microbiome changes in stroke have demonstrated decreases in both commensal and beneficial genera, increases in pathogenic genera in human patients (Swidsinski et al, 2012;Yin et al, 2015), and substantial changes in the phylum Firmicutes, Bacteroidetes, and Actinobacteria in stroke mice (Singh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that adjustments in the gut microbiome influence ischemic brain injury by altering immune homeostasis (Benakis et al, 2016;Singh et al, 2016) and neuroprotective cytokine production (Benakis et al, 2016). This suggests that the gut microbiome is another potential therapeutic target for stroke (Benakis et al, 2016;Singh et al, 2016Singh et al, , 2018Winek et al, 2016;Benakis et al, 2020). Studies of gut microbiome changes in stroke have demonstrated decreases in both commensal and beneficial genera, increases in pathogenic genera in human patients (Swidsinski et al, 2012;Yin et al, 2015), and substantial changes in the phylum Firmicutes, Bacteroidetes, and Actinobacteria in stroke mice (Singh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the main obstacle to the clinical translation of microbiome study is the large variability between patients' intestinal microbiomes, which cannot be easily reproduced with animal models. Nevertheless, microbiome-based treatments can have a huge impact on improving post-stroke outcomes in the future [34,87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate the effect of intestinal microflora on a host stroke outcome, paying attention to two-way communication along the brain-gut axis [28,34]. Growth of Bacteroidetes after an ischemia was confirmed in monkeys [35].…”
Section: Post-ischemic Brain Versus Gut Microbiotamentioning
confidence: 93%
See 1 more Smart Citation
“…Different studies observed an overall reduction of the Firmicutes, with a concomitant overgrowth of Bacteroidetes (Singh et al 2016 ; Spychala et al 2018 ). However, when analyzing microbiota changes at lower taxonomic ranks, there is a lack of consistency regarding the specific bacterial changes in clinical and experimental stroke (Benakis et al 2020a , b ). Differences in the location of fecal sampling (across the GI tract in mice, and stool samples in patients), the methods used for the extraction of genomic DNA and for 16S rRNA gene analysis, the severity of the stroke model and the baseline differences in the microbiota composition (the mouse origin or inter- and intra-individual variabilities in humans) could be confounding factors accounting for the contradictory results (Costello et al 2009 ; Sadler et al 2017 ; Stanley et al 2018 ).…”
Section: Stroke Alters Microbiota Compositionmentioning
confidence: 99%